Murine model of cross-IgE sensitization and cross-anaphylactic reactions among multiple group food allergens - Musa, Ibrahim; Ardalani, Fariba; Yang, Nan; Maleki, Soheila J.; Li, Xiu-Min (Frontiers in Immunology, 2025)
RationaleApproximately 32 million people in the United States suffer from food allergies. Some food groups, such as legumes – peanuts, tree nuts, fish, and shellfish, have a high risk of cross-reactivity. However, the murine model of multiple food group cross-reactivity is limited.ObjectiveWe sought to develop a murine model that can be used to investigate novel therapeutics for the treatment of multiple food allergies.MethodsC3H/HeJ mice were sensitized intraperitoneally (i.p.) once a week for three weeks with a mixture of 500µg of protein from peanut, cashew, walnut, shrimp, cod, and 2 mg Alum. The control group consisted of naïve mice. IgE levels against the sensitized allergens and their cross-reactive allergens were measured by ELISA at baseline and 3 weeks after sensitization. In weeks 4 and 5, the mice were given intragastric challenges with 200mg/mouse of each food: peanut, chickpea, lentil, cashew, almond, pistachio, hazelnut, brazil nut, walnut, pecan, shrimp, lobster, cod, salmon, and mackerel. After each challenge, anaphylactic symptoms, rectal temperatures, and plasma histamine were measured.ResultsThere was a significant elevation of IgE against sensitized antigens (peanut cashew, walnut, shrimp, and cod) as well as cross-reactive allergens used for oral food challenge from legumes including peanut, chickpea, and lentil, as well as tree nuts such as cashew, almond, pistachio, hazelnut, brazil nut, walnut, and pecan. Furthermore, there was a significant increase in crustaceans such as shrimp, lobster and fish like cod, salmon, and mackerel (p<0.01). Consistently, significantly increased anaphylactic symptom scores (p<0.05), decreased rectal temperature (p<0.001), and increased plasma histamine (p<0.05) compared to the naïve mice occurred following each challenge with sensitized foods and unsensitized, but cross-reactive foods.ConclusionWe generated a comprehensive murine model of IgE-mediated multiple food groups of cross-reactive anaphylaxes. This will provide an essential tool for developing novel therapies for cross-reactivity multiple food allergies.